ANALYSIS OF THE INTERFERENCE IMPACT ON THE TRANSMISSION RATE OF G.FAST BROADBAND ACCESS SYSTEMS - Oreshkov, Vasyl; Balashov, Vitalii; Hynda, Valentyna; Zapotichnyi, Denys (Sworld-Us Conference proceedings, 2025)
The paper presents an analysis of the interference impact on the transmission rate of G.fast transmission systems. Operation scenarios of G.fast transmission systems over TPP 10×2×0.4 and UTP Cat5e 4×2×0.5 cables using orthogonal harmonic signals of a gen